Increased healthcare costs for filaggrin‐related eczema and asthma: hope for targeted management and prevention. (1st September 2018) - Akiyama, M.; Bray, N.
Abstract: Linked Article: Soares et al. Br J Dermatol 2018; 179 :717–723 .